Cultural Representation of Chinese-Indonesians in Ca Bau Kan (The Courtesan) in the Context of Spice Trading and Nationalism - Anton Sutandio; Yohan Yusuf Arifin (k@ta: A Biannual Publication on the Study of Languange and Literature, 2022)
The object of this research is Nia Dinata’s film, Ca Bau Kan, which was adapted from Remy Sylado’s novel. The research focuses on the representation of Chinese-Indonesians which pertains to the context of the maritime spice trade route and the concept of nationalism. Set in Batavia in three different decades, namely the 1930s, 1940s, and 1960s, the film depicts the journey of a Chinese-Indonesian character from the Dutch colonial era and the Japanese colonial era to the era of the independence revolution. The research method used is a qualitative method through the theory of film studies, which is juxtaposed with the historical approach to see how Chinese-Indonesians are represented in the film. The findings show that the film attempts to represent the Chinese-Indonesians accurately, albeit with the continuous presence of inaccurate stereotypes. The findings show Chinese-Indonesians’ economic contribution that reflects the history of the spice trade maritime route in Indonesia.